If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -12x = 3x + 32 Reorder the terms: 7 + -12x = 32 + 3x Solving 7 + -12x = 32 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + -12x + -3x = 32 + 3x + -3x Combine like terms: -12x + -3x = -15x 7 + -15x = 32 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + -15x = 32 + 0 7 + -15x = 32 Add '-7' to each side of the equation. 7 + -7 + -15x = 32 + -7 Combine like terms: 7 + -7 = 0 0 + -15x = 32 + -7 -15x = 32 + -7 Combine like terms: 32 + -7 = 25 -15x = 25 Divide each side by '-15'. x = -1.666666667 Simplifying x = -1.666666667
| -5q=-30 | | (-4mn^2)(2m^4n^2)= | | 4p+9=1 | | 2x^2+12=-20 | | -4(4v+4)=-112 | | B-4/6=b/-2 | | -6y+7x=30 | | 8y+3=15+7y | | 1-7k=16-4k | | 9x*(-4)= | | 2(3r-v)= | | 8+m=2m-3 | | 2(x-1)=2x+-2 | | x^2+10=-26 | | X-3=6+4 | | 4+2(x+1)+6=14 | | 1+(5q-w)= | | V-(3n+x)= | | 7p-26=107 | | 6-4(x-3)=2x-1 | | x=-2y-7 | | -.2(3+a)=-4 | | (3x-2w)-q= | | X(x-12)+15=-4x | | 16c^4+12b^3=0 | | Y=3/4•9/2 | | 12x+12=-9x+15-4x | | y= 0.05 x + 25 | | 12x+12=-3x+15-4x | | 5v-10/v-6=5/2 | | 35z+4(7z-42)=18(2z-3) | | f(x)=-5+2 |